The Pacific perspective: coal development in British Columbia, 1981-2000 - John Clancy; Andrew J. Freyman (Canadian Institute of Mining, Metallurgy and Petroleum, 1982)
"Trends in world coal markets indicate that the next twenty years could be a period of intensive development for British Columbia's coal resource. This paper examines demand projections for metallurgical, thermal and chemical feedstock coals, with particular reference to domestic and Pacific Rim markets. Supply possibilities, from the point of view of British Columbia's competitive position, are explored, with emphasis on the interaction of such factors as capital, labour, port and transportation requirements.The paper concludes with an examination of British Columbia's strategies in light of the foregoing, and comments on the government's role in ensuring that development of the coal resource be attained in a manner consistent with over-all provincial goals and objectives.IntroductionFor the purposes of this paper the Pacific Rim is defined as including, in addition to Canada, the following: Japan, Korea, the People 's Republic of China, Hong Kong, Taiwan, the countries of the Indonesian Archipelago, Australia, New Zealand and the Pacific-bordering countries of South America and Mexico. The United States has been excluded in this definition in order to better illustrate the economic growth potential for British Columbia coal in the Pacific Rim economies.In the past decade, the Pacific Rim economies have grown faster than most other economies in the rest of the world; economic growth rates of 10 per cent were common in the region prior to the 1974 slowdown and the average rate of economic expansion in the mid-1970s has exceeded 6 per cent. Rapid expansion of international trade in the region has been a major stimulus in this process. By 1979, Pacific Rim two-way trade has reached an estimated $550 billion-about 20 per cent of world trade."